Oral literary traditions in North Sumatra - Papenhuyzen, Clara Brakel (UI Scholars Hub, 2010)
This article deals with traditional literature of the Pakpak-Dairi and Karo peoples in North Sumatra, who are speakers of closely related Batak languages and have many common features in their language and culture. Their traditional life-style, based on agriculture and the use of forest products, requires the regular performance of community rituals featuring songs, dance, music and other oral traditions including storytelling. The songs, prayers, and stories belonging to their literary tradition have characteristic features that are intimately connected with the social context in which they are created and performed. Karo and Pakpak-Dairi oral genres often contain information about the natural environment, local customs and religious concepts. They may also reflect perceptions of relationships with neighbouring groups, such as the Minangkabau and the Malays who live in the coastal areas.